Diversification outbreaks and dynamics of Asian leaf-litter frogs, genus Leptobrachella (Anura, Megophryidae), with the description of a new species from Guizhou Province, China - Tao Luo; Zi-Fa Zhao; Zhong-Lian Wang; Chang-Ting Lan; Ming-Yuan Xiao; Huai-Qing Deng; Ning Xiao; Jiang Zhou (Zoosystematics and Evolution)
The uplift of the Qinghai-Tibet Plateau and the Indochina extrusion are two of the most prominent consequences of the India–Asia collision. These two geologic events greatly altered topography and drainage patterns that, in turn, affected the regional climate, the landscape and the evolution of biodiversity. Despite this, little is known about how orogeny and climate affect the evolution of biodiversity, especially the dynamics of diversification, including origins, peaks and endings. Here, we performed phylogenetic and biogeographic analyses of Leptobrachella distributed in Southeast Asia and southern China, based on mitochondrial 16S ribosomal RNA. The results revealed that Leptobrachella may be roughly divided into Clade I from south of the Indo-Burma and Clade II from central and northern Indo-Burma and southern China. We then investigated the diversification of Leptobrachella over time through biogeographic meta-analyses. We showed that the speciation of Leptobrachella was dominated by in situ diversification that was most likely associated with the uplift of the Qinghai–Tibet Plateau, the Indochina extrusion and the intensification of the Asian monsoon and that diversification may have been less influenced by temperature. In situ diversification experienced three small accelerated phases and one decelerated phase initiated at ~ 32 Ma, with a sharp increase at ~ 15 Ma, a peak at ~ 8.7 Ma and a gradual decline after ~ 6 Ma and the peaks of diversification were asynchronous in Southeast Asia and southern China. Our results suggest a three-phase scenario for the diversification of Leptobrachella, with periods of acceleration and deceleration at every stage, a pattern consistent with the Indochina extrusion, the uplift of the Qinghai–Tibet Plateau and the intensification of the Asian monsoon since the Oligocene. This study highlights how biogeographic meta-analyses can be utilised to estimate diversification history in taxa lacking sufficient molecular markers to quantify the impact of orogeny and climatic shifts on diversification processes. In addition, we also identified four undescribed species and described one new species, Leptobrachella xishuiensis sp. nov., from Xishui County, Guizhou Province, China.